1994
DOI: 10.2307/3431822
|View full text |Cite
|
Sign up to set email alerts
|

Summary of the National Toxicology Program Benzidine Dye Initiative

Abstract: The benzidine dye initiative is a research program established by the National Toxicology Program to generate an integrated body of scientific information regarding the potential health risks associated with exposure to benzidine-and benzidine-congener-derived dyes. Because an indepth evaluation of each of the hundreds of benzidine-congener-derived dyes was considered impractical, the research program was designed to study the metabolism and disposition, genetic toxicity, and in vivo toxicity and carcinogenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
10
0
2
Order By: Relevance
“…Some azo dyes are not normally toxic but the amines resulting from the anaerobic digestion of these substances may possess these characteristics . Some authors have found that the cleavage of azo bonds in benzidine based azo dyes or direct dyes produce benzidine and 4‐aminobiphenyl which are classified as carcinogenic and mutagenic . Table presents studies of the degradation of different direct dyes and their by‐products in reactors with different configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Some azo dyes are not normally toxic but the amines resulting from the anaerobic digestion of these substances may possess these characteristics . Some authors have found that the cleavage of azo bonds in benzidine based azo dyes or direct dyes produce benzidine and 4‐aminobiphenyl which are classified as carcinogenic and mutagenic . Table presents studies of the degradation of different direct dyes and their by‐products in reactors with different configurations.…”
Section: Introductionmentioning
confidence: 99%
“…La mesure de la teneur en hémoglobine dans ces milieux biologiques relève de plusieurs techniques : spectrophotométrie directe (Wians et al, 1988), spectrophotométrie dérivée (Taulier et al, 1986 ;Copeland et al, 1989), chimiluminescence (Olsson et al, 1982), turbidimétrie (Engler et al, 1979) et colorimétrie (Ahlquist et Schwartz, 1975 ;Slaunwhite et al, 1979 ;Fairbanks et al, 1992). Les méthodes colorimétriques, plus usuelles, se font sur le plasma et mettent à profit l'activité peroxydasique de l'hémoglobine qui oxyde un chromogène (Fairbanks et al, 1992 ;Morgan et al, 1994;Dionne, 2006). La benzidine, premier chromogène utilisé s'est révélée cancérigène (Kum-Tatt et Ling, 1969 ;Morgan et al, 1994 ) ; elle a été alors remplacée par ses dérivés qui le sont moins comme l'attestent plusieurs études (Lijana et Williams, 1979 ;Levinson et Goldman, 1982 ;Pillier-Loriette et al, 1983 ;Takayanagi et Yashiro, 1984).…”
Section: Introductionunclassified
“…Les méthodes colorimétriques, plus usuelles, se font sur le plasma et mettent à profit l'activité peroxydasique de l'hémoglobine qui oxyde un chromogène (Fairbanks et al, 1992 ;Morgan et al, 1994;Dionne, 2006). La benzidine, premier chromogène utilisé s'est révélée cancérigène (Kum-Tatt et Ling, 1969 ;Morgan et al, 1994 ) ; elle a été alors remplacée par ses dérivés qui le sont moins comme l'attestent plusieurs études (Lijana et Williams, 1979 ;Levinson et Goldman, 1982 ;Pillier-Loriette et al, 1983 ;Takayanagi et Yashiro, 1984).…”
Section: Introductionunclassified
“…Benzidine has been used for the production of azo dyes, which are widely applied in the textile, paper, and leather industries (Morgan et al. 1994; Chung et al.…”
Section: Introductionmentioning
confidence: 99%